2017
DOI: 10.3748/wjg.v23.i24.4407
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for metachronous gastric carcinoma development after endoscopic resection of gastric dysplasia: Retrospective, single-center study

Abstract: AIMTo determine the gastric adenocarcinoma (GAC) occurrence rate and related factors, we evaluated the follow-up results of patients confirmed to have gastric dysplasia after endoscopic resection (ER).METHODSWe retrospectively analyzed the medical records, endoscopic examination records, endoscopic procedure records, and histological records of 667 cases from 641 patients who were followed-up for at least 12 mo, from among 1273 patients who were conformed to have gastric dysplasia after Endoscopic mucosal rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Although the reported progression rates varied in different studies, patients with HGD had higher rates of progression to invasive carcinoma (10%-68.8%) than those with LGD (2.8-11.5%) [3][4][5][6][7] . A recent study reported that HGD was a significant risk factor for the development of metachronous gastric cancer after ESD of gastric dysplasia (odds ratio, 2.74; P = 0.023 vs. LGD) 12 . Similarly, in the present study, the risks of MGNs (HR, 1.45; P = 0.425), and metachronous HGD or gastric cancer (HR, 2.42; P = 0.214) were increased in the HGD group compared with the LGD group; however, there were no statistical significances between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the reported progression rates varied in different studies, patients with HGD had higher rates of progression to invasive carcinoma (10%-68.8%) than those with LGD (2.8-11.5%) [3][4][5][6][7] . A recent study reported that HGD was a significant risk factor for the development of metachronous gastric cancer after ESD of gastric dysplasia (odds ratio, 2.74; P = 0.023 vs. LGD) 12 . Similarly, in the present study, the risks of MGNs (HR, 1.45; P = 0.425), and metachronous HGD or gastric cancer (HR, 2.42; P = 0.214) were increased in the HGD group compared with the LGD group; however, there were no statistical significances between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, long-term surveillance endoscopy after ER of gastric dysplasia should focus on high-risk patients to increase cost-effectiveness. Risk factors associated with metachronous neoplasm or EGC after ER for gastric dysplasia were male sex 12 , old age 14,16 , open-type atrophic gastritis 15 , presence of intestinal metaplasia 12,14 , and HGD 12 . However, the reported risk factors were numerous and inconsistent among different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For diagnosis of gastric dysplasia, specimens obtained by endoscopic biopsy are not representative of the entire lesion, and histological discrepancies have been reported between biopsy specimens and resected ones [ 1 ]. Therefore, endoscopic resection (ER) is recommended for gastric dysplasia, not only for removal of the lesion but also for its exact diagnosis [ 2 ]. As gastric dysplasia poses a risk of metachronous gastric cancer, surveillance after ER is important.…”
mentioning
confidence: 99%
“…Interestingly, most of the the newly detected lesions showed the same endoscopic and histopathological types as those of the primary lesions in this study. However, a previous study reported that most metachronous gastric adenocarcinomas occurred at sites other than the previous resection sites [ 2 ]. Therefore, more studies are necessary to clarify the findings of this study.…”
mentioning
confidence: 99%